KARAKTERISTIK DAN TEMPERATUR BAWAH PERMUKAAN FLUIDA PANAS BUMI GUNUNG SLAMET DAN SEKITARNYA, JAWA TENGAH - Khilal Khoiri Polanunu; Johanes Hutabarat; Agus Didit Haryanto; Dewi Gentana (PPSDM Geominerba, 2021)
Administratively the area of Mount Slamet is located in Central Java Province. The area has geothermal potential. The purpose of research is to find out the geochemical characteristics of water (type, origin, and equilibrium) and estimate of subsurface temperature (reservoir) geothermal by using methods of observation in the field and analysis of data from the geochemical laboratory results of hot springs. The results showed that the characteristics of the geothermal fluids type from MAPS and MAPP13 were bicarbonate water with the condition as pheripiral waters. MAPCB as a chloride sulfate water type with conditions as steam heated water, while MAPTH as a chloride water type in absorption of low B/Cl steam conditions with dominant Cl content become mature water. The origin of the MAPS, MAPCB, MAPP13 fluids are formed under conditions of absorption of high B/Cl steam with a dominant B content which are interpreted as originating from geothermal fluid, and when they moving to the surface the fluid interacts with the side rocks in its path. In addition, MAPS, MAPCB, MAPP13 are also included in the immature waters zone with high Mg content. This indicates that the three hot springs have intensive experienced mixing and dilution of shallow groundwater rich in Mg. Then, based on the difference in the concentration ratio of Cl/B in hot springs, the research area is interpreted have two reservoirs, namely reservoir A and reservoir B. Then, based on the calculation of the fluid geothermometer, it is estimated that reservoir A has temperature ranges from 149o -158oC, while reservoir B has temperature ranges from 89o -116oC.